2017
DOI: 10.1016/j.jocs.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of optic disc, fovea and retinal vasculature using a single convolutional neural network

Abstract: We have developed and trained a convolutional neural network to automatically and simultaneously segment optic disc, fovea and blood vessels. Fundus images were normalized before segmentation was performed to enforce consistency in background lighting and contrast. For every effective point in the fundus image, our algorithm extracted three channels of input from the point's neighbourhood and forwarded the response across the 7-layer network. The output layer consists of four neurons, representing background, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(94 citation statements)
references
References 54 publications
1
85
0
1
Order By: Relevance
“…In the field of ophthalmology, this study is the first to compare the performance of state-of-the-art object-detection architectures. There have been two major studies to date: one 21,22 involved object detection of the ONH in an entire fundus photograph, and the other 2,23,24 involved classification of the ONH in a cropped image. Object detection involves not only classifying every object in an image but also localizing them by drawing the appropriate bounding box.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of ophthalmology, this study is the first to compare the performance of state-of-the-art object-detection architectures. There have been two major studies to date: one 21,22 involved object detection of the ONH in an entire fundus photograph, and the other 2,23,24 involved classification of the ONH in a cropped image. Object detection involves not only classifying every object in an image but also localizing them by drawing the appropriate bounding box.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the cascade classifier performed well for high-quality images, the performance was significantly degraded for lower-quality images. Tan et al 22 reported segmentation of the ONH, fovea, and retinal vasculature using a single CNN. The localization accuracy (IoU) of segmenting the ONH was 0.6210.…”
Section: Discussionmentioning
confidence: 99%
“…The DL algorithms have shown promising performance comparable to expert segmentation in fundus images [28,38]. The most unique advantage of DL is the ability to precisely learn and capture a huge amount of image features with varying hierarchies and locations.…”
Section: Research and Clinical Implicationsmentioning
confidence: 99%
“…These limitations can be overcome by utilizing some pre-processing steps in the future. Tan et al [49] implemented a seven-layer-based convolutional neural network (CNN) for the segmentation of retinal vessels and reported a classification accuracy of 94.54%. Wang et al [50] also used a CNN model with ensemble learning for vessel segmentation.…”
Section: Blood Vessel Extractionmentioning
confidence: 99%